The Intervening Role of Job Satisfaction in the Relationship between Organizational Support and Burnout - Putri Sartika Siregar; Meutia Nauly; Filia Dina Anggaraeni (CV. Era Digital Nusantara, 2026)
This study addresses the growing issue of employee burnout in high-demand organizational environments, particularly within the financial service sector. The objective of this research is to examine the effect of perceived organizational support on burnout and to analyze the mediating role of job satisfaction among employees of PT Pegadaian. A quantitative explanatory research design was employed using survey data collected from employees through structured questionnaires. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) to test both direct and indirect relationships among variables. The results reveal that perceived organizational support has a significant negative effect on burnout, indicating that higher levels of organizational support reduce employees’ psychological exhaustion. Additionally, perceived organizational support has a significant positive effect on job satisfaction, suggesting that supportive organizational practices enhance positive work attitudes. Job satisfaction also shows a significant negative effect on burnout, confirming its role as a protective psychological factor. Importantly, the findings demonstrate that job satisfaction partially mediates the relationship between perceived organizational support and burnout. This indicates that organizational support reduces burnout not only directly but also indirectly through increasing job satisfaction. These findings highlight the importance of strengthening organizational support systems and enhancing job satisfaction as strategic approaches to reducing burnout and improving employee well-being. The study contributes to the literature by providing empirical evidence on the mediating mechanism of job satisfaction in the relationship between organizational support and burnout within a state-owned enterprise context.